Rumah Moderasi Beragama di PTKIN: Potret Kebijakan dan Strategi Mewujudkan Beragama Moderat di Perguruan Tinggi - Rambe, Toguan; Mawardi, Mawardi; Mayasari, Seva (Abrahamic Religions: Jurnal Studi Agama-Agama, 2023)
This article is the result of research on the existence of religious moderation houses (RMB) at PTKIN. Based on the circular from the Ministry that the existence of a religious moderation house has an important role in providing education and strengthening the understanding of religious moderation for State Islamic Religious Colleges (PTKIN). In its position, each PTKIN provides a wide space for religious moderation houses to play an active role and contribute to academic and non-academic activities. Data collection in this study was carried out by direct interviews and focus group discussions with the chairman and administrators of the house of religious moderation (RMB) at UIN North Sumatra Medan and UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan. The results of this study include the formation of the management of the house of moderation in religion which has been carried out based on the Chancellor's decree at each tertiary institution. The activities carried out are related to socializing the urgency of religious moderation in the tertiary environment, including organizing seminars and workshops that are held entitled religious moderation. Providing ToT (Training of Trainer) training for lecturers and students so that they become agents of religious moderation, collaborating with FKUB as a religious institution that already exists and forming religious moderation villages as fostered villages as a way to spread religious moderation to the community.AbstrakArtikel ini merupakan hasil penelitian terhadap eksistensi rumah moderasi beragama (RMB) di PTKIN. Berdasarkan ederan dari Kementerian bahwa keberadaan rumah moderasi beragama memiliki peranan penting dalam memberikan edukasi dan penguatan pemahaman moderasi beragama bagi Perguruan Tinggi Keagamaan Islam Negeri (PTKIN). Dalam kedudukannya setiap PTKIN memberikan ruang yang begitu luas terhadap rumah moderasi beragama berperan aktif dan memberikan kontribusinya terhadap kegiatan akademik maupun non akademik. pengumpulan data dalam penelitian ini dilaksanakan dengan wawancara langsung dan focus group discussion dengan ketua dan pengurus rumah moderasi beragama (RMB) di UIN Sumatera Utara Medan dan UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan. Hasil dari penelitian ini antara lain pembentukan kepengurusan rumah moderasi beragama telah dilaksanakan berdasarkan surat keputusan Rektor pada masing-masing perguruan tinggi. Adapun kegiatan yang dilakukan terkait mensosialisasikan urgensi moderasi beragama dilingkungan perguruan tinggi antara menata kegiatan seminar maupun workshop yang dilaksanakan bertajuk moderasi beragama. Memberikan pelatihan ToT (Training of Trainer) bagi dosen dan mahasiwa sehingga menjadi agen moderasi beragama, melaksanakan kerjama dengan FKUB sebagai institusi keagamaan yang sudah eksis serta membentuk kampung moderasi beragama sebagai desa binaan sebagai jalan menyebarkan moderasi beragama bagi masyarakat.